2011
DOI: 10.1128/jvi.02130-10
|View full text |Cite
|
Sign up to set email alerts
|

Unmasking the Active Helicase Conformation of Nonstructural Protein 3 from Hepatitis C Virus

Abstract: The nonstructural protein 3 (NS3) helicase/protease is an important component of the hepatitis C virus (HCV) replication complex. We hypothesized that a specific ␤-strand tethers the C terminus of the helicase domain to the protease domain, thereby maintaining HCV NS3 in a compact conformation that differs from the extended conformations observed for other Flaviviridae NS3 enzymes. To test this hypothesis, we removed the ␤-strand and explored the structural and functional attributes of the truncated NS3 protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
41
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(48 citation statements)
references
References 55 publications
7
41
0
Order By: Relevance
“…Ding et al (15) have recently reported enzymatic data supporting a fully open form as proposed by Brass et al (4).…”
supporting
confidence: 54%
“…Ding et al (15) have recently reported enzymatic data supporting a fully open form as proposed by Brass et al (4).…”
supporting
confidence: 54%
“…This difference may be explained by the conformation-dependent binding of the APHI to NS3, in which the APHI targets a site in the interdomain interface that is present in the compact crystallographic conformation of NS3 but not in the extended conformation, which biochemical studies suggest represents the active conformation during RNA synthesis (30). Partial inhibition of RNA synthesis by AT23708 is consistent with NS3 adopting the extended conformation at least some of the time during RNA synthesis.…”
Section: Discussionmentioning
confidence: 57%
“…This model predicts that the protease domain is anchored tightly against the membrane and is free to rotate only in the plane parallel to the membrane surface. Previous structural and biochemical work on NS3 from HCV, dengue virus, and Murray Valley encephalitis virus indicates that the ϳ10-amino-acid linker region between the protease and helicase domains can accommodate a rotation of up to 180°between domains (93)(94)(95). This flexibility is sufficient for placement of adjacent NS3 helicase domains and would allow both domains to orient themselves above the membrane (Fig.…”
Section: Discussionmentioning
confidence: 98%